Quality of home stimulation and language development in children aged 12-24 months living in orphanages and family homes - Yuridyah P. Mulyadi; Soedjatmiko Soedjatmiko; Hardiono D. Pusponegoro (Indonesian Pediatric Society Publishing House, 2009)
Background  Language development  is  fundamental for children's intellectual development. Therefore, early stimulation in the first  three  years  of  life play an  important  role especially in disadvantaged communities such  as  foster homes. Objective  To  determine  the  quality  of  home stimulation  and language development, and their correlations in children living in orphanages  and  family homes. Methods  This study was conducted between December  2007  and January  2008.  Subjects were recruited from several orphanages in Jakarta, Tangerang, Bogor, also three posyandus in Jakarta and Tangerang.  The  quality  of  home stimulation was assessed using Home  Stimulation  Observation  for  the  Measurement  of  the Environment (HOME) scores, while language development was assessed using Clinical Linguistic and Auditory Milestone Scale Development  Quotient  (CLAMS  DQ). Results  A total  of  80  healthy children, consisting  of  40  children in orphanages  and  40  in family homes were enrolled. Inadequate stimulation and language delay were found  to  be significantly higher in the orphanage group  (52.5%  vs.  27.5%; P=0.022  and 57.5%  vs.  10%; P<0.001,  respectively).  HOME  Scores  and CLAMS  DQ  were also significantly lower in  the  orphanage group compared to those  in  the family home group  (25.6  vs 31.5; P<0.001  and  84.0  vs  110.7; P=0.002).  Logistic regression revealed  that  caregiver-child  attachment  time was  the  only risk factor  for  language delay  (OR  32.32; P<0.0001),  in  both orphanages and family homes. Result  The  quality of home stimulation  is  lower in the orphanages, which results in a higher rate  of  language delay  in  children aged 12-24  months.